2021
DOI: 10.1093/nar/gkab109
|View full text |Cite
|
Sign up to set email alerts
|

TbSAP is a novel chromatin protein repressing metacyclic variant surface glycoprotein expression sites in bloodstream form Trypanosoma brucei

Abstract: The African trypanosome Trypanosoma brucei is a unicellular eukaryote, which relies on a protective variant surface glycoprotein (VSG) coat for survival in the mammalian host. A single trypanosome has >2000 VSG genes and pseudogenes of which only one is expressed from one of ∼15 telomeric bloodstream form expression sites (BESs). Infectious metacyclic trypanosomes present within the tsetse fly vector also express VSG from a separate set of telomeric metacyclic ESs (MESs). All MESs are silenced in bloods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…While metacyclic VSG genes were upregulated in I-BET151 treated insect stage parasites, we detected no differences in the expression of procyclin (Supplemental Figure 2), indicating that extensive remodeling of the cell surface is unlikely to occur following bromodomain inhibition. TbSAP1 was recently identified as an important repressor of metacyclic VSG expression 22 . We observed reasonably high and unvarying transcript levels of TbSAP1 following bromodomain inhibition, and it's possible that the presence of this protein prevented sufficient expression of metacyclic VSG genes to support surface remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While metacyclic VSG genes were upregulated in I-BET151 treated insect stage parasites, we detected no differences in the expression of procyclin (Supplemental Figure 2), indicating that extensive remodeling of the cell surface is unlikely to occur following bromodomain inhibition. TbSAP1 was recently identified as an important repressor of metacyclic VSG expression 22 . We observed reasonably high and unvarying transcript levels of TbSAP1 following bromodomain inhibition, and it's possible that the presence of this protein prevented sufficient expression of metacyclic VSG genes to support surface remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated that there are a large number of histone interacting proteins that form specific complexes in bloodstream forms, and that many of these complexes localize to sites of transcription initiation and termination 17 . Perturbation of histone interacting complexes in trypanosomes has been shown to affect immune evasion [18][19][20][21][22][23] , cell cycle 24 , and differentiation processes [23][24][25] .…”
mentioning
confidence: 99%
“…Inducible transcript knockdown was performed using the pDEX-V4-Pex11 RNAi construct (gift of Bill Wickstead) 52 . Sense and anti-sense fragments of at least 500 bp of the target gene CDS were cloned flanking Pex11 using conventional cloning (Supplementary Table S5 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another more recent screen for loss-of-silencing of a telomeric selectable marker adjacent to a metacyclic VSG promoter yielded TbSAP, a chromatin-associated negative regulator [70]. The bloodstream VSGs are co-transcribed with several expression-site associated genes or ESAGs.…”
Section: Gene Expression Control Mechanismsmentioning
confidence: 99%